Síntese de derivados 4-aril-3,4-di-hidrocumarínicos catalisada por NbCl5 - Santos, Willian Henrique dos [UNESP]; Siqueira, Mayara de Souza [UNESP]; Silva Filho, Luiz Carlos da [UNESP] (Sociedade Brasileira de Química, 2013)
Multicomponent reactions between phenols, β-diesters and benzaldehydes for the synthesis of 4-aryl-3,4-dihydrocoumarin derivatives were carried out under mild conditions (room temperature) and presented moderate yields (38-88%) and reasonable reaction times (2-4 days), using niobium pentachloride as a catalyst.
Synthesis of 4-aryl-3,4-dihydrocoumarin derivatives catalyzed by NbCl5
Keywords: niobium pentachloride; multicomponent reaction; coumarin derivatives